2013
DOI: 10.1016/j.acvd.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the measurement of the abdominal aortic diameter by novice operators using a pocket-sized ultrasound system

Abstract: In order to screen for abdominal aortic aneurysm, the abdominal aortic diameter can be accurately measured by non-specialist physicians with pocket-sized ultrasound devices after a short period of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 18 publications
0
34
0
2
Order By: Relevance
“…Bonnafy et al [40] found that abdominal aortic measurements performed by trained medical students were similar to those obtained by experts. Durham [41] describes three situations where hand-held ultrasound administered by non-experts has saved time and had clinical benefits: ectopic pregnancy, AAA, and pericardial effusion.…”
Section: Discussionmentioning
confidence: 91%
“…Bonnafy et al [40] found that abdominal aortic measurements performed by trained medical students were similar to those obtained by experts. Durham [41] describes three situations where hand-held ultrasound administered by non-experts has saved time and had clinical benefits: ectopic pregnancy, AAA, and pericardial effusion.…”
Section: Discussionmentioning
confidence: 91%
“…It may be true that compared to a certified experienced technician, a POCUS novice will produce tests with lower sensitivity and specificity (810). However, some research has shown that this is not always the case (11). We advocate that bedside ultrasound should not be considered an alternative to formal technician-acquired radiologist-interpreted ultrasound studies, and its test characteristics should not be compared with these exams (12).…”
Section: Discussionmentioning
confidence: 99%
“…Screening for abdominal aortic aneurysms in elderly patients may be integrated into the clinical examination performed by cardiologists [10,32], and is accessible after a short period of training [33]. Accuracy with pocket-echocardiography is generally good [10,32,33] ( Table 1).…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%